The Impact of Cloud-Based Point-of-Sale (POS) Technology on the Quality of Financial Reports in MSMEs - Wahyu Setyawan; Loggar Bhilawa (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of perceived ease of use and perceived usefulness of cloud-based Point of Sale (POS) technology on the financial report quality of Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage sector in Surabaya City. This research method uses a quantitative approach with primary data obtained through a questionnaire using a Likert scale of 1 – 4. The population in the study was all MSMEs in the Food and Beverage sector in Surabaya City. The sample used in this study were MSME owners who have used or understand cloud-based POS systems, selected using purposive sampling. The number of samples used in this study was 397 respondents. Data analysis was carried out using multiple linear regression with the Statistical Product and Service Solution (SPSS) method. The result of the study indicates that perceived ease of use and perceived usefulness have a positive and significant effect both partially and simultaneously on the financial report quality of MSMEs. These findings confirm that easy-to-use and beneficial cloud-based POS systems improve the relevance, reliability, and timeliness of financial reports, implying that local governments should provide practical training and technical assistance to accelerate MSME digital transformation.